The effect of entrepreneurship training on the capacity building program of Kano state enterprise development training institutes - Muazu, Muazu Hassan; Ibrahim, Najafi Auwalu (Construction Research Institute of Malaysia (CREAM), 2017)
Kano state enterprise development training institutes were established with the expectation to further promote and increase the number of small enterprises owners, improve the sustenance of small businesses, and reduce unemployment in the society.The institutes have graduated many students some of whom have ventured into businesses and others did not start any.Even those that have started hardly sustaining them beyond six months.It is against this backdrop, the study therefore aimed at understanding the effect of entrepreneurship training on the capacity building program with concerns to training quality, trainers competence, and availability and functionality of training facilities in the institutes.A survey research design was used, hence primary data were collected through questionnaire. A sample of 370 respondents were selected using convenient sampling technique. With the use of multiple regression analysis, the results of the study showed that training quality, trainers competence and training facilities have significant effect on capacity building effectiveness. The study thus recommended that the training institutes should standardise the admission process, curricula and improve on post training support activities.They should also determine trainers training needs and should send them for further training.The institutes should provide up-to-date training facilities with effective maintenance mechanism.Also, the study make some recommendations for future studies to in-corporate other effective variables like government political will and funding that could explain the remaining variance in capacity building effectiveness.